The cisA cistron of Bacillus subtilis sporulation gene spoIVC encodes a protein homologous to a site-specific recombinase. - Sato, T (1990)
The nucleotide sequence of the sporulation gene spoIVC cisA in Bacillus subtilis was determined and found to encode a protein of 500 amino acid residues with a calculated molecular weight of 57,481, which is in good agreement with the size of the gene product estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The amino acid sequence of the N-terminal region of this protein is homologous to the site-specific DNA recombinases. Hybridization of a 3.6-kilobase EcoRI fragment carrying the spoIVC cisA gene with the EcoRI-restricted chromosomal DNA prepared from cells of various stages showed that DNA rearrangement occurs only in the mother cell in the region adjacent to spoIVC cisA 3 h after the initiation of sporulation. This result coincides with that of Stragier et al. (P. Stragier, B. Kunkel, L. Kroos, and R. Losick, Science 243:507-512, 1989). The timing of the DNA rearrangement coincides very well with the timing of spoIVC cisA gene expression. The DNA rearrangement was not observed in spoIVC cisA mutants. These results strongly suggest that the spoIVC cisA gene encodes a site-specific DNA recombinase having a very important role in sporulation.